Epidemiological Evaluation of Activities of Daily Living among disabled population in a rural area of Uttarakhand - Shilpee; Vyas, Shaili; Kumar Srivastava, Ashok; Sharma, Neha (Indian Journal of Community Health, 2020)
Introduction- In India, Disability remains about the able-bodied. The disabled person frequently describes limitations in their activities of daily living (ADL). Although few studies have discussed about ADL among disabled but in rural setting it is still unexplored. Thus the objective of the study was to assess the dependency of disabled persons according to ADL. And to find the association between each ADL item with the socio-demographic findings. Methodology- A cross-sectional study compromising of 2600 study participants aged 5-59 years were recruited through multi-stage random sampling technique in a rural area of district Dehradun. Chi-square and Fischer exact test analysis was used to analyse the association among activities of daily living (ADL) with socio-demographic variables. Result- The overall prevalence of disability among both male and females was 2.3 %. 20-39 years age-group was mostly affected. Among ADL most of the disabled were fully dependent on others for grooming & bathing. Age, religion, education and occupation were statistically significant with the ADL. Conclusion- Better health policies, Training of family members to provide support to disabled persons and Promotion of home-based occupations should be executed. To improve ADL and QOL of disabled people education, employment, non-discrimination, vocational training and rehabilitative services should be strengthened.